Effect Of Puerperium, Estrus Synchronization And Postbreeding Periods On Plasma Profile Of Total Protein, Cholesterol And Triglycerides In Gir Cows - Krishnan, Ammu Rama; Dhami, A.J.; Naikoo, M.; Patel , S.B.; Savalia , F.P. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
This study was carried out on 24 Gir cows of 2nd to 4th parity from calving till 140 days postpartum on an organized farm. The objective was to monitor the plasma total protein, cholesterol and triglyceride profile at 10 days interval during first 90 days postpartum and then during various estrus synchronization (CIDR, Ovsynch and Cosynch) protocols till 40 days post-AI. The behavioural estrus induction response was observed in 83.33, 83.33 and 100.00 % of cows under CIDR, Ovsynch and Co-synch protocols, respectively. The conception rates at induced estrus (FTAI) in CIDR, Ovsynch and Cosynch protocol were 50.00, 50.00 and 33.33 %, respectively. The corresponding overall conception rates of 2 cycles post-treatment were 83.33 (5/6), 66.66 (4/6) and 83.33 % (5/6). In control group, the first service and overall conception rates were 33.33 and 66.66 (4/6) %, respectively. The overall pooled mean values of total protein, cholesterol and triglyceride varied between intervals from calving till 90 days postpartum in the range of 5.82 ± 0.19 to 6.44 ± 0.15 g/dl, 79.66 ± 2.70 to 190.57 ± 8.84 mg/dl and 16.31 ± 0.86 to 21.53 ± 1.59 mg/dl, respectively. The values of cholesterol varied significantly between periods in all the 4 groups, including pooled values and that of triglycerides showed significant difference only in CIDR group. None of the three parameters were influenced by estrus induction/ synchronization protocols, during treatment or till 40 days post-AI. The biochemical investigations helped to conclude that the selected animals in all hormone protocols and control group were healthy and were maintained under optimum nutritional regime, and this was probably the reason, why their profile was not influenced by the various estrus induction and synchronization protocols used.
Keywords: Gir cows; Puerperal period; Estrus synchronization; Plasma protein; Cholesterol; Triglycerides